Staggered overdose pattern and delay to hospital presentation are associated with adverse outcomes following paracetamol‐induced hepatotoxicity - Craig, Darren G. N.; Bates, Caroline M.; Davidson, Janice S.; Martin, Kirsty G.; Hayes, Peter C.; Simpson, Kenneth J. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ON THIS SUBJECT • Paracetamol hepatotoxicity is the commonest cause of acute liver failure (ALF) in the UK. • Relatively little is known regarding the impact of staggered overdose pattern or delayed hospital presentation upon subsequent mortality or need for emergency liver transplantation. WHAT THIS STUDY ADDS • Staggered paracetamol overdoses, frequently taken to relieve pain, are strongly associated with reduced survival compared with single time point overdose. • Staggered paracetamol overdoses should be treated as high risk for the development of multiorgan failure, and should be considered for N‐acetyl cysteine treatment irrespective of admission serum paracetamol concentrations. • The King's College poor prognostic criteria may have reduced sensitivity in staggered overdose patients. AIMS Paracetamol (acetaminophen) poisoning remains the major cause of severe acute hepatotoxicity in the UK. In this large single centre cohort study we examined the clinical impact of staggered overdoses and delayed presentation following paracetamol overdose. RESULTS Between 1992 and 2008, 663 patients were admitted with paracetamol‐induced severe liver injury, of whom 161 (24.3%) had taken a staggered overdose. Staggered overdose patients were significantly older and more likely to abuse alcohol than single time point overdose patients. Relief of pain (58.2%) was the commonest rationale for repeated supratherapeutic ingestion. Despite lower total ingested paracetamol doses and lower admission serum alanine aminotransferase concentrations, staggered overdose patients were more likely to be encephalopathic on admission, require renal replacement therapy or mechanical ventilation and had higher mortality rates compared with single time point overdoses (37.3% vs. 27.8%, P= 0.025), although this overdose pattern did not independently predict death. The King's College poor prognostic criteria had reduced sensitivity (77.6, 95% CI 70.8, 81.5) for this pattern of overdose. Of the 396/450 (88.0%) single time point overdoses in whom accurate timings could be obtained, 178 (44.9%) presented to medical services >24 h following overdose. Delayed presentation beyond 24 h post overdose was independently associated with death/liver transplantation (OR 2.25, 95% CI 1.23, 4.12, P= 0.009). CONCLUSIONS Both delayed presentation and staggered overdose pattern are associated with adverse outcomes following paracetamol overdose. These patients are at increased risk of developing multi‐organ failure and should be considered for early transfer to specialist liver centres.